2013
DOI: 10.1182/blood.v122.21.640.640
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Induction Regimen and Consolidative Stem Cell Transplantation In Patients With Double Hit Lymphoma (DHL): A Large Multicenter Retrospective Analysis

Abstract: Background DHL are high-grade B-cell lymphomas (BCL) characterized by dual gene rearrangements (RA) of MYC and either BCL2 or BCL6. Outcomes are typically dismal, particularly when treated with R-CHOP, as compared to those observed in patients (pts) with similar histologies without dual RA. Few reports have evaluated the use of intensive induction regimens, with or without consolidative stem cell transplantation (SCT). We sought to evaluate the role of intensive induction as well as SCT, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Overall, the current meta‐analysis included 394 patients. The 2 largest studies, reported by Oki et al () and Gandhi et al (), accounted for more than half of these patients. The majority of patients with DHL had stage III/IV disease, intermediate or high International Prognostic Index score and elevated serum lactate dehydrogenase at first diagnosis.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall, the current meta‐analysis included 394 patients. The 2 largest studies, reported by Oki et al () and Gandhi et al (), accounted for more than half of these patients. The majority of patients with DHL had stage III/IV disease, intermediate or high International Prognostic Index score and elevated serum lactate dehydrogenase at first diagnosis.…”
Section: Resultsmentioning
confidence: 96%
“…However, the study did report the number of patients at risk at each time point, so the number of censored and observed events within each time interval was able to be calculated (Appendix S1). In the remaining five studies, DHL‐ and treatment‐specific KM curves were either not reported or were illegible to determine individual event or censoring times (Abramson et al , ; Gandhi et al , ; Navarro et al , ; Sun et al , ; Cohen et al , ). Thus, aggregate survival data were used for these studies and were incorporated into the model as median survival time or percent surviving at follow‐up time (Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…68 Given the retrospective nature of these reports, it is very likely that the patients who received escalated induction therapy, HDT-ASCT, and/or allo-SCT were chosen based on such fea-tures as younger age, better performance status, and (in the case of SCT) based on response to induction therapy, each of which correlates with more favorable disease characteristics and with improved clinical outcomes. Moreover, the lack of a survival benefit associated with escalated induction regimens observed in the studies by Gandhi and colleagues and Oki et al, 56,67 despite favorable CR rates, suggests that relapse of DHL offsets most, if not all, early benefit of intensification. The role of escalated induction therapy for those patients who have double-expressing lymphoma or DHL, as defined by MYC GOC criteria, remains poorly explored.…”
Section: Management Considerations In Non-bl Myc-associated Lymphoma mentioning
confidence: 99%
“…Existing data suggest that this is a rare phenomenon and carries a poor prognosis, although whether such patients fare worse than those with DHL is not known. 55,56 The observation that IHC routinely detects a greater proportion of both MYC and BCL2 overexpression compared with FISH techniques raises an important question: is expression of both MYC and BCL2 protein (as detected by IHC) prognostically relevant independent of genetic rearrangements? In fact, there is now a growing body of data supporting the notion that patients with this socalled double protein-expressing or, simply, double-expressing lymphoma have a poor prognosis on par with FISHdefined DHL; however, there is significant discordance on the degree of immunohistochemical positivity associated with adverse outcomes.…”
Section: Double-hit Lymphomas/petrich Et Almentioning
confidence: 99%
“…Accordingly, there is a strong rationale for offering intensive first‐line therapies to patients with MYC‐ rearranged DLBCL (including DH), and the use of dose‐adjusted EPOCH‐R (etoposide, predisone, vincristine, cyclophosphamide, doxorubicin, rituximab; NCT01092182) is currently being evaluated in a multi‐centre phase 2 clinical trial. Consolidative haematopoietic cell transplantation in first remission may lead to prolonged overall survival in DH lymphoma patients, although the benefit of this strategy remains unclear (Gandhi et al , ; Howlett et al , ; Oki et al , ). Furthermore, preclinical data suggests that newly‐developed BCL2 antagonists, such as the BH3‐mimetics, have activity in BCL2/MYC overexpressing mouse models with and without the addition of other anti‐lymphoma therapy (Mason et al , ; Vandenberg & Cory, ).…”
mentioning
confidence: 99%